`f(x)=ln(ln(ln(x))) `. To find the domain of `f(x)` we need to solve the inequality `ln(ln(x))>0 `. Take the exponential on both sides, `e^(ln(ln(x)))>e^0=>ln(x)>1=>e^(ln(x))>e^1=>x>e `. The plot shows this result:

Next, we need to apply the Chain rule multiple times, keeping in mind the derivative of `ln(x)` which is `1/x `. Thus,

`d/dx f(x) = (1)/(ln(ln(x)))(ln(ln(x)))' = `

`(1)/(ln(ln(x)))*(1)/(ln(x))(ln(x))'= `

`(1)/(ln(ln(x)))*(1)/(ln(x))*1/x = (1)/(x ln(x) ln(ln(x)))`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now